Advokasi dan Penyuluhan Kriminalitas di Kalangan Remaja Tanganapada Baubau - Sarif Sarif; Harlianto Harlianto; Riduwan Riduwan; Nashatun Nashatun (Jurnal Kabar Masyarakat, 2023)
This study aims to explore the role of advocacy and counseling in preventing juvenile delinquency in Baubau, a city facing challenges in addressing the high crime rates involving youth. This research uses a qualitative method with a case study approach from several schools and communities in Baubau. Data were collected through interviews with teenagers, educators, and relevant parties, as well as field observations. The research results show that advocacy and counseling programs involving parents, teachers, and other stakeholders have proven effective in raising youth awareness about the legal and social consequences of criminal actions. Despite this, the main challenge faced is the lack of community involvement as a whole and the limited funding and resources for these programs. This research suggests the need for a more holistic approach and continued efforts in crime prevention among the youth, by strengthening cooperation between the government, educational institutions, and the community.